The NADPH Link between the Renin Angiotensin System and the Antioxidant Mechanisms in Dopaminergic Neurons - Rafael Franco; Joan Serrano-Marín; Gemma Navarro; Rafael Rivas-Santisteban (MDPI AG, 2023)
The renin angiotensin system (RAS) has several components including signaling peptides, enzymes, and membrane receptors. The effort in characterizing this system in the periphery has led to the approval of a class of antihypertensives. Much less is known about RAS in the central nervous system. The production of RAS peptides and the expression of several RAS enzymes and receptors in dopaminergic neurons of the substantia nigra has raised expectations in the therapy of Parkinson's disease, a neurodegenerative condition characterized by lack of dopamine in the striatum, the motor control region of the mammalian brain. On the one hand, dopamine production requires reducing power. On the other hand, reducing power is required by mechanisms involved in REDOX homeostasis. This review focuses on the potential role of RAS in the regulation of neuronal/glial expression of glucose-6-phosphate dehydrogenase, which produces the NADPH required for dopamine synthesis and for reactive oxygen species (ROS) detoxification. It is known that transgenic expression of the gene coding for glucose-6-phosphate dehydrogenase prevents the death of dopaminergic nigral neurons. Signaling via angiotensin II G protein-coupled receptors, AT1 or AT2, leads to the activation of protein kinase A and/or protein kinase C that in turn can regulate glucose-6- phosphate dehydrogenase activity, by Ser/Thr phosphorylation/dephosphorylation events. Long-term effects of AT1 or AT2 receptor activation may also impact on the concentration of the enzyme via activation of transcription factors that participate in the regulation of gene expression in neurons (or glia). Future research is needed to determine how the system can be pharmacologically manipulated to increase the availability of NADPH to neurons degenerating in Parkinson's disease and to neuroprotective glia.